Comparison of standard and standard plus vitamin E therapy for Helicobacter pylori eradications in children - Tümgör, Gökhan; Baran, Masallah; Çakır, Murat; Yüksekkaya, Hasan Ali; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Although various drugs can be used in adults for Helicobacter pylori eradication in adults, treatment options are limited in children. The aim of this study was to compare the effects of the standard lansoprazole, amoxicillin, and clarithromycin (LAC) protocol to those of LAC + vitamin E (LACE) combination for H. pylori eradication. Materials and Methods: The study included 90 children (age range: 10-17 years) who were admitted to four pediatric gastroenterology centers between March 2011 and November 2012 with dyspeptic symptoms and who had tested positive for H. pylori by 14C-urea breath tests. The patients were randomized into two groups. The LAC group [45 patients (pts)] was treated with a standard regimen consisting of lansoprazole (1 mg/kg/day), amoxicillin (50 mg/kg/day), and clarithromycin (14 mg/kg/day), each of which was given in two equally divided doses every 12 h for 14 days; the LACE group (45 pts) was given the standard regimen and vitamin E at 200 IU/day for 14 days. H. pylori eradication was assessed using the 14C-UBT in the 6th week after the cessation of treatment. Results: H. pylori was eradicated in 21 (46.6%) pts in the LAC group, while it was eradicated in 29 (64.4%) pts in the LACE group. There was no statistical difference between the two groups (p=0.13). Conclusion: The eradication rate of H. pylori in children while using the LAC regimen has decreased in the last years. The LACE regimen has been associated with an increased eradication rate but can reach to statistically significance. Further studies with larger cohorts are needed to examine the success of the LACE regimen for H. pylori eradication.